IPTEKS PEMBERIAN DANA BANTUAN SOSIAL PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) PROVINSI SULAWESI UTARA - Kantohe, Anastasia J.; Lumingkewas, Gloria S.; Nangoi, Grace B. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Social Assistance is the provision of assistance in the form of money or goods from the government for the people who need it which aims to protect from the occurrence of social risks. The provision of social assistance funds is carried out based on the provisions or rules stated in the law. The method used in this study is evaluating the provision of social assistance funds in accordance with Permendagri No 32 Tahun 2011. The object studied was in North Sulawesi BPKAD. The technique used in evaluating this is to make a comparison of the procedures for granting social assistance funds by North Sulawesi BPKAD in accordance with Permendagri No 32 Tahun 2011. The result of this research indicate that the implementation of the provision of social assistance funds in North Sulawesi BPKAD is in accordance with Permendagri No 32 Tahun 2011.Keywords: Evaluating, Social Assistance, BPKAD